Thinking Aloud: An exploration of cognitions in professional snooker. (May 2018) - Welsh, James C.; Dewhurst, Stephen A.; Perry, John L.
Abstract: Objectives: Presently, there is no exploration into the cognitive processes of super-elite and elite professional snooker players during real-time performance. Therefore, this study explored the cognitions of seven professional snooker players during real-time solo practice performance. Design: A Think Aloud (TA) protocol analysis. Method: This involved players verbalizing and explaining their thoughts within naturalistic practice environments. Player's verbalizations were recorded during each solo practice performance, transcribed verbatim, and analyzed via protocol analysis. Results: Analyses revealed an array of continuous reactive-adaptive cognitions relating to stressors and coping strategies during performance, as well as general snooker-specific related thoughts. Specifically, the results highlighted key stressor themes which were coded as: Table Conditions, Distractions, and Mistakes. Our main finding was: Shot Preparation being essential to problem-focused coping, with Rationalizing integral to emotion-focused coping. Further results highlighted the visual-perceptual and cognitive expertise of players, with regards to identification of problem balls and cueball spatial awareness, insofar as unearthing the deliberate structure to practice routines. Conclusions: The study's original and novel findings lend further support to the transactional process of coping. Whilst accordingly, the utilization of TA significantly contributed to our limited understanding of super-elite and elite real-time cognitions in professional snooker and self-paced sports generally. Future research should continue to dissect the sport-specific nuances that underpin real-time performance, not only during practices, but within competitive play. TA is an appropriate methodology to use in the domain-specific sport of snooker. Highlights: Think Aloud protocol is a feasible method to collect real-time cognitions during solo practice performances in snooker. Real-time cognitive processes change continuously during solo practice performances in professional snooker. Problem-focused strategies are key for consistent and optimal performances in professional snooker. Future research should utilize Think Aloud protocol to explore problem-focused strategies during competitive play.